Healthy food and cultural holism. (May 2016) - Kim, Sang-Yeon; Lim, Tae-Seop; Song, Hayeon; Cramer, Emily M.; Ahn, Seokhoon; Kim, Jihyun; England, Nathan; Kim, Hyun-Joo; Kim, Junghyun
Abstract: Adopting Nisbett's theory of analytic and holistic thinking, the current study examines cultural influence on perceptions about the health benefits of holistic foods and nutritional elements. Consistent with the theory, Korean older adults ( n = 84) tended to believe that consuming whole, natural foods (e.g., honey, aloe vera, green tea) is more helpful for health than taking individual nutrition elements (e.g., vitamins, calcium, iron). A reverse pattern prevailed for American older adults ( n = 61). Results from a follow-up study ( n = 284) indicate the same pattern of cultural difference in perception of food nutrition can be replicated with individual measurements of analytic-holistic thinking. Holistic thinking tended to predict the valuation of food functions (' what it does as a whole ') and the de valuation of food elements (' what is in it '). The current findings extend the validity of Nisbett's theory and provide practical implications for medical doctors and food marketers intending to persuade Asian patients/clients.